2016
DOI: 10.1038/srep38729
|View full text |Cite
|
Sign up to set email alerts
|

The known genetic loci for telomere length may be involved in the modification of telomeres length after birth

Abstract: Telomere length varies considerably among individuals. It is highly heritable and decreases with ageing or ageing related diseases. Recently, genome-wide association studies (GWAS) have identified several genetic loci associated with telomere length in adults. However, it is unclear whether these loci represent the genetic basis of telomere length or determine the individual susceptibility to shortening during growth process. Using DNA extracted from peripheral and cord blood of 444 mother-newborn pairs from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(52 reference statements)
2
15
0
Order By: Relevance
“…We also observed that during fetal development, telomere length improves in cord blood; thus, mothers had a shorter length than a cord in our study which has also been observed by Weng et al (p < 0.001) [50].…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that during fetal development, telomere length improves in cord blood; thus, mothers had a shorter length than a cord in our study which has also been observed by Weng et al (p < 0.001) [50].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies indicated that rs10936599 in TERC was associated with telomere length and with an increased risk of cancers, but the conclusions were inconsistent [ 20 , 25 , 26 ]. To date, there no report on the association between rs10936599 and lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible reasons for this might be the heterogeneity between populations, as studies were performed in healthy African-American children and adolescents [57] and in a healthy European population [58]. Genotyping of the SNPs identified in the European cohort was also performed in newborns in an Asian population, but no significant association for any individual variant was detected [59].…”
Section: Genetic Determinants Of Tlmentioning
confidence: 99%